INCLUSIVE COMMUNITY DEVELOPMENT IN ACTION: THE ROLE OF COMMUNITY-BASED REHABILITATION AND EMPOWERMENT STRATEGIES - Neni Anggraeni; Sri Nurhayati; Gumpanat Boriboon (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study investigates the persistent challenge of advancing sustainable disability inclusion in rural Indonesia by critically examining participatory, community-based approaches through a qualitative case study method. The research aims to elucidate how locally embedded methodologies—specifically participatory rural appraisal, bottom-up planning, and cross-sectoral stakeholder engagement—can address the structural and cultural barriers that marginalize children with disabilities and their families. Employing an interpretive case study design, data were collected via in-depth interviews, focus group discussions, and documentary analysis to generate a nuanced understanding of the lived experiences and collaborative processes among beneficiaries, practitioners, and local policymakers engaged in community-based disability programs. The findings demonstrate that the integration of participatory methodologies within multi-level partnerships is fundamental to shifting social attitudes, reducing stigma, and embedding inclusive practices within local policy and governance. The deliberate involvement of families, particularly mothers and children with disabilities, emerged as both a key driver and tangible outcome of empowerment and social transformation.